Answer :

Given that P(E1) =P1 and P(E2) =P2


=P(E1). P(E2) =P (E1 Ո E2)

So, E1 and E2 occur simultaneously.

(ii)(1-P1) P2

As we know P(A)+P(A) = 1

=P(E1)’. P(E2)

= P (E1’ Ո E2)

So, E1 does not occur but E2 occur.

(iii)1-(1-P1) (1-P2)

As we know P(A)+P(A) = 1


=1-P (E1’ Ո E2’)

By De Morgan’s laws:

=1-P (E1 Ս E2)

As we know P(A)+P(A) = 1

= 1- [1-P (E1 Ս E2)]

= P (E1 Ս E2)

So, either E1 or E2 or both E1 and E2 occurs.


= P(E1) + P(E2) – 2P(E1) P(E2)

= P(E1) + P(E2) – 2P (E1 Ո E2)

= P (E1 Ս E2)- 2P (E1 Ո E2)

So, either E1 or E2 occurs but not both.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

A bag contains 6 RD Sharma - Volume 2

A man is known toMathematics - Board Papers

A bag contaRD Sharma - Volume 2

Three persons A, Mathematics - Board Papers

Bag I contains 3 Mathematics - Board Papers

A speaks trRD Sharma - Volume 2

Two cards aRD Sharma - Volume 2

A bag contaRD Sharma - Volume 2

Kamal and MRD Sharma - Volume 2

Two balls aRD Sharma - Volume 2